Diversity of Lepidoptera: Rhopalocera at Selorejo Waterfall Area, Ponorogo District, East Java, Indonesia - Zulaikha, Siti; Susanto, Muhamad Azmi Dwi (Universitas Negeri Surabaya, 2021)
Selorejo Waterfall is a natural tourist area that is directly adjacent to the Sigogor Mountain Nature Reserve and has a beautiful and natural environment. This makes the Selorejo Waterfall area has a good environment for the sustainability of various species of butterflies. This research aimed to find out the diversity and abundance of butterflies in the Selorejo Waterfall area. This research was conducted using the Visual Day Flaying method by following the trail in the Selorejo Waterfall area. This study found 26 species belongs 4 families with 109 individuals in total. The value of the species diversity index at the location of H'= 2.81 moderate category. The diversity of butterflies in the Selorejo Waterfall area was influenced by the availability of host plants and feed as well as abiotic factors.